2019
DOI: 10.1080/2162402x.2019.1665973
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use and the efficacy of immune checkpoint inhibitors in cancer patients: a pooled analysis of 2740 cancer patients

Abstract: The gut microbiota plays a critical role in the anti-tumor immune response. There is increasing data showing that antibiotics (ATBs) change the composition of the gut microbiota and affect the efficacy of immune checkpoint inhibitors (ICIs). However, this is the first meta-analysis to evaluate the association between ATB use and ICI efficacy in cancer patients to provide a better understanding of the strength of this association. We performed a literature search for relevant studies that evaluated the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 40 publications
4
75
1
Order By: Relevance
“…6 Similarly, several studies have shown that antibiotic use just before initiation and during immune checkpoint inhibitors (ICI) use was associated with shorter progression-free survival (PFS) and overall survival (OS) in patients with nonsmall cell lung cancer (NSCLC), renal cell cancer (RCC), urothelial cancer and melanoma. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In contrast to solid tumours treated with ICI, the success of cytotoxic chemotherapy in acute myeloid leukaemia (AML) depends on non-immune direct cytotoxicity, and thus, would not be expected to be changed by potential microbiota-mediated immune effects. However, the intestinal microbiota can modify antineoplastic effects of some chemotherapeutic agents.…”
Section: Key Questionsmentioning
confidence: 99%
“…6 Similarly, several studies have shown that antibiotic use just before initiation and during immune checkpoint inhibitors (ICI) use was associated with shorter progression-free survival (PFS) and overall survival (OS) in patients with nonsmall cell lung cancer (NSCLC), renal cell cancer (RCC), urothelial cancer and melanoma. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In contrast to solid tumours treated with ICI, the success of cytotoxic chemotherapy in acute myeloid leukaemia (AML) depends on non-immune direct cytotoxicity, and thus, would not be expected to be changed by potential microbiota-mediated immune effects. However, the intestinal microbiota can modify antineoplastic effects of some chemotherapeutic agents.…”
Section: Key Questionsmentioning
confidence: 99%
“…The gut microbiota play a role in the response and resistance to immunotherapy (2,(4)(5)(6). Gut dysbiosis caused by antibiotics impairs response to ICB, suggesting that an intact gut microbiota is essential to improve the efficacy of ICB and an attractive therapeutic target for cancer treatment (1,3,4,7). Manipulating commensal microbiota enhances the efficacy of ICB in murine models (2,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…After early encouraging reports showing that the use of anthracyclines such as doxorubicin, epirubicin or idarubicin to treat various tumor types resulted in the potentiation of the patient's anti-tumor immunity [133], and data from other studies showed that antibiotic treatment had no deleterious effects on the response of non-small cell lung carcinomas (NSCLC) to treatment with the immune checkpoint inhibitor (ICI) nivolumab [134,135], results from preclinical chemo-immunotherapy protocols combining cyclophosphamide chemotherapy with adoptive T-cell (ACT) immunotherapy, using a mouse model of B-cell lymphoma, demonstrated that prophylactic use of broad-spectrum antibiotics reduced the efficacy of cyclophosphamide and impaired the therapeutic effects of ACT [136]. Since then, most studies have reported negative effects of antibiotic exposure leading to diminished levels of efficacy of ICIs in immunotherapy protocols for the treatment of a variety of tumors, including lung tumors/NSCLC [137][138][139][140][141][142][143][144], advanced or metastatic renal cell carcinoma [137,141,142,144], urothelial carcinoma [141], and melanoma [141,143,144]. In addition, more recently, it has been reported that antibiotic use had a negative impact on the response of patients with locally advanced head-and-neck tumors to treatment protocols involving chemotherapy or radiotherapy [145].…”
Section: Antibiotics and Cancer Therapy Outcomesmentioning
confidence: 99%